2011
DOI: 10.1371/journal.pone.0027401
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent Dual Effects of Hydrogen Peroxide on Insulin Signal Transduction in H4IIEC Hepatocytes

Abstract: BackgroundOxidative stress induced by the accumulation of reactive oxygen species (ROS) has a causal role in the development of insulin resistance, whereas ROS themselves function as intracellular second messengers that promote insulin signal transduction. ROS can act both positively and negatively on insulin signaling, but the molecular mechanisms controlling these dual actions of ROS are not fully understood.Methodology/Principal FindingsHere, we directly treated H4IIEC hepatocytes with hydrogen peroxide (H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 29 publications
1
83
0
2
Order By: Relevance
“…This again underscores the complexity of the ROS regulation on GSIS, and may be explained by the concentration-dependent dual effect of H 2 O 2 (29 (18) in the SKO and dKO islets. However, selenite did not affect GSIS of the WT and GKO islets, which was different from that reported in rat islets and min6 cells (13).…”
Section: Figmentioning
confidence: 69%
See 1 more Smart Citation
“…This again underscores the complexity of the ROS regulation on GSIS, and may be explained by the concentration-dependent dual effect of H 2 O 2 (29 (18) in the SKO and dKO islets. However, selenite did not affect GSIS of the WT and GKO islets, which was different from that reported in rat islets and min6 cells (13).…”
Section: Figmentioning
confidence: 69%
“…Thus, the relatively low expression of antioxidant enzymes in islets (39) may not only render them susceptible to oxidative insults, but also provide a necessary metabolic condition for their sensitive responses to reactive oxygen species (ROS)-mediated signaling in GSIS (49). In fact, hydrogen peroxide (H 2 O 2 ) functions as an essential second messenger (19) in initiating and regulating GSIS (49,50), and it demonstrates concentration-dependent dual effects on insulin signaling and other metabolic processes (29,51).…”
Section: Introductionmentioning
confidence: 99%
“…A direct link between mitochondrial H 2 O 2 production and JNK1 activation has not yet been demonstrated, but an inverse relationship between protein tyrosine phosphatase PTP-1B activity and JNK1 activation has been shown by treating H4IIEC hepatocytes with increasing concentrations of H 2 O 2 (Iwakami et al 2011). With relatively low concentrations of H 2 O 2 (≤5.0 μM), PTP-1B activity was inhibited and insulin-stimulated phosphorylation IRS and Akt was enhanced.…”
Section: Impairment Of Insulin Signalingmentioning
confidence: 99%
“…ROS have been implicated in the regulation of several processes such as cytokine secretion, proliferation, differentiation, gene expression and as cytotoxic molecules in immune responses against invading pathogens (Hensley et al, 2000). A study with H4IIEC hepatoma cells showed that different H 2 O 2 concentrations could either enhance, if in a low concentration such as 5 μm, or repress, if in a high concentration such as 50 μm, the insulin signaling pathway (Iwakami et al, 2011). Remarkably, adipocytes seem to adapt to dynamic changes in ROS levels and to use them as second messengers.…”
Section: Requirement Of Ros For Adipogenesis and Insulin Signalingmentioning
confidence: 99%